Perception of difficult patient and coping methods in primary healthcare institutions - Karahuseyinoglu, Ebru Koktepe; Oguzoncul, Ayse Ferdane (Bayrakol Medical Publisher, 2021)
Aim: Although there is no definitive definition of the concept of difficult patient, patients with behavior that hinders communication are characterized as difficult patient by the most general definition we encounter in the literature. In this study, it is intended to determine the sociodemographic characteristics of difficult patients most frequently encountered by healthcare workers, and to investigate the discomfort felt by the employees during difficult patient interviews and methods of coping with difficult patients. Materials and Methods: The universe of the research consisted of 268 healthcare workers working in primary health care institutions located in Elazig city center. Without going to sample selection, reaching the entire universe was targeted, and 248 (92.5%) healthcare workers were reached. In the research, a Questionnaire of Difficult Patient was created and used as a data collection tool, including 38 questions, validity and reliability of which were made by us and determined as a result of a comprehensive literature review. Each expression was examined in 4 dimensions as follows: 'Patient's Difficulty, Discomfort Felt by the Staff, Compliance and Communication Problems, and Seductive Behaviors' with a 5-point Likert scale. Besides, in the questionnaire, there were the sections that questioned the demographic characteristics of participants and difficult patients and also two open-ended questions for measuring the incidence of a difficult patient and determining methods of coping with difficult patients. Results: According to the healthcare workers participated in the study, the most frequently encountered sociodemographic characteristics of difficult patients were determined as follows: 50,4 % were male, 44,8% young-adult, 85.1% married, 32.7% primary and secondary school graduates, 62.5% were at middle socioeconomic level, 30.6% homemakers, 29% officers, and 87,1% were from the city. It was observed that as a method of coping with difficult patients, healthcare workers mostly preferred to try to understand and communicate correctly. Discussion: The mean dimensions of the patient's difficulty, discomfort felt by the staff, and compliance and communication problems were calculated above 3, which was the midpoint, and the mean dimension of seductive behaviors was below 3. This indicates that healthcare professionals are very uncomfortable with difficult patients and have difficulty communicating with them. In our study, it was remarkable that female employees considered female patients, male employees considered male patients, and healthcare workers at the high school, associate, and an undergraduate level also considered more male patients as a difficult patient. Moreover, the present study draws attention to the efforts of employees to understand difficult patients, communicate with them, and act calmly and patiently, their willingness at a lower rate, even to a small extent, to refer patients, and the fact that they preferred legal ways by calling security.
Keywords: Difficult patient; Patient communication; Coping methods